Improving Reducibility of Iron Ore Pellets by Optimization of Physical Parameters - PAL, JAGANNATH; Ghorai, S; Ammasi, A; Hota, S K; Koranne, V M; Venugopalan, T (Journal of Mining and Metallurgy, Section B: Metallurgy, 2016)
Reducibility of iron bearing material is an important property which represents its suitability of reduction in iron making furnaces. It has direct influence on improving productivity and lowering energy consumption in iron making process. The reducibility of iron ore pellets of a specific chemistry can be improved by the optimization of physical parameters such as induration temperature, improving size distribution of fines, improving apparent porosity etc. In this study, the reference pellet is prepared in a typical plant condition and the properties of the reference pellet are considered as base value to improve reducibility index (RI) maintaining other properties at the acceptable limit without altering pellet chemistry. Optimization of induration temperature at the 1250-1275 ºC shows around 74 % RI, which is 5 points more than the base value of 69.5%. Furthermore, on optimizing additives size, such as limestone fines and anthracite coal fines at -350 mesh and induration temperature of 1250-1275 ºC, RI is improved to 77%, i.e., 8 points improvement is achieved with respect to the base value.